Answer:
To simplify the given equation, we can start by using the rules of algebra to rearrange the terms and combine like terms on both sides of the equation. This gives us:
-x - (-4x - 6) = 6
We can then distribute the negative sign on the left side of the equation to get:
-x + 4x + 6 = 6
We can then combine like terms on the left side of the equation to get:
3x + 6 = 6
We can then subtract 6 from both sides of the equation to get:
3x = 0
We can then divide both sides of the equation by 3 to get the final result:
x = 0
Therefore, the simplified form of the given equation is x = 0.
Explanation: